Anatomic repair of a chronic distal biceps tendon rupture: a case report - Tuteja, Sanesh; Rodricks, Timothy (International Journal of Research in Orthopaedics, 2025)
Chronic distal biceps tendon ruptures, common in weightlifting, pose significant challenges for surgical repair due to the high demands placed on the biceps muscle. Traditional repair techniques, such as direct suture fixation, may be inadequate for athletic patients. This case report presents a novel approach using the modified Boyd-Anderson two-incision technique, incorporating an endobutton and fiberloop to enhance tendon stability and functional recovery. A 40-year-old male weightlifter with a chronic distal biceps rupture underwent surgical repair after physical examination and imaging confirmed the injury. The modified Boyd-Anderson technique, involving two incisions, allowed optimal tendon exposure. An endobutton was used to secure the tendon to the radial tuberosity, while a fiberloop reinforced the repair. The procedure, performed under general anesthesia, minimized soft tissue damage. Postoperative rehabilitation focused on strength training and follow-up at 2 months showed significant improvement in range of motion, strength and overall function, enabling the patient to return to daily activities. This technique, with its use of the endobutton and fiberloop, provides a promising option for anatomical repair of chronic distal biceps ruptures in athletic individuals, offering effective restoration of function and strength. It underscores the importance of customized surgical approaches for tendon repair in active patients.